Aminooxy‐naphthylpropionic acid and its derivatives are inhibitors of auxin biosynthesis targeting l‐tryptophan aminotransferase: structure–activity relationships. (18th July 2016) - Narukawa‐Nara, Megumi; Nakamura, Ayako; Kikuzato, Ko; Kakei, Yusuke; Sato, Akiko; Mitani, Yuka; Yamasaki‐Kokudo, Yumiko; Ishii, Takahiro; Hayashi, Ken‐ichiro; Asami, Tadao; Ogura, Takehiko; Yoshida, Shigeo; et al.
Significance Statement: It is difficult to evaluate the functions of auxin and the biosynthesis pathways of indole‐3‐acetic acid using genetic approaches; chemical genetics is an alternative method. Here we show that L‐α‐aminooxy‐phenylpropionic acid (AOPP), an inhibitor of auxin biosynthesis, targets tryptophan aminotransferase. We synthesized novel compounds derived from AOPP to study the structure–activity relationships of inhibitors of tryptophan aminotransferase in vitro, and identified some that were more potent, and more specific, in inhibiting auxin levels. We designate these compounds 'pyruvamines'. Summary: We previously reportedl ‐α‐aminooxy‐phenylpropionic acid (AOPP) to be an inhibitor of auxin biosynthesis, but its precise molecular target was not identified. In this study we found that AOPP targets TRYPTOPHAN AMINOTRANSFERASE of ARABIDOPSIS 1 (TAA1). We then synthesized 14 novel compounds derived from AOPP to study the structure–activity relationships of TAA1 inhibitors in vitro . The aminooxy and carboxy groups of the compounds were essential for inhibition of TAA1 in vitro . Docking simulation analysis revealed that the inhibitory activity of the compounds was correlated with their binding energy with TAA1. These active compounds reduced the endogenous indole‐3‐acetic acid (IAA) content upon application to Arabidopsis seedlings. Among the compounds, we selected 2‐(aminooxy)‐3‐(naphthalen‐2‐yl)propanoic acid (KOK1169/AONP) and analyzed its activities in vitro and in vivo . Arabidopsis seedlings treated with KOK1169 showed typical auxin‐deficient phenotypes, which were reversed by exogenous IAA. In vitro and in vivo experiments indicated that KOK1169 is more specific for TAA1 than other enzymes, such as phenylalanine ammonia‐lyase. We further tested 41 novel compounds with aminooxy and carboxy groups to which we added protection groups to increase their calculated hydrophobicity. Most of these compounds decreased the endogenous auxin level to a greater degree than the original compounds, and resulted in a maximum reduction of about 90% in the endogenous IAA level in Arabidopsis seedlings. We conclude that the newly developed compounds constitute a class of inhibitors of TAA1. We designated them 'pyruvamine'.